2009
DOI: 10.1523/jneurosci.1710-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid-Dependent Homeostatic Regulation of Inhibitory Synapses by Miniature Excitatory Synaptic Activities

Abstract: Homeostatic regulation of synaptic strength in response to persistent changes of neuronal activity plays an important role in maintaining the overall level of circuit activity within a normal range. Absence of miniature EPSCs (mEPSCs) for a few hours is known to cause upregulation of excitatory synaptic strength, suggesting that mEPSCs contribute to the maintenance of excitatory synaptic functions. In the present study, we found that the absence of mEPSCs for 1-3 h also resulted in homeostatic suppression of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 70 publications
2
27
0
Order By: Relevance
“…Recent studies have shown that spontaneous release also contributes to several other synaptic effects, including some cases of homeostatic scaling (7)(8)(9)(10)(11)(12)(13)(14). Scaling in those cases has additional similarities to intermediate-and long-term facilitation: Both types of plasticity can involve postsynaptic Ca 2+ (8,23,33), protein synthesis (8,23,34), AMPA receptor insertion (7,8,16,33), and modulation of the presynaptic probability of release (10)(11)(12)15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that spontaneous release also contributes to several other synaptic effects, including some cases of homeostatic scaling (7)(8)(9)(10)(11)(12)(13)(14). Scaling in those cases has additional similarities to intermediate-and long-term facilitation: Both types of plasticity can involve postsynaptic Ca 2+ (8,23,33), protein synthesis (8,23,34), AMPA receptor insertion (7,8,16,33), and modulation of the presynaptic probability of release (10)(11)(12)15).…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, we have learned that spontaneous release can contribute to postsynaptic firing (2, 3), regulation of postsynaptic kinase pathways (4), and maintenance of postsynaptic dendritic spines and receptors (5,6). Spontaneous release has also been found to contribute to some cases of homeostatic scaling of synaptic strength (7)(8)(9)(10)(11)(12)(13)(14). Here we report a role of spontaneous transmitter release in the induction of a learning-related form of synaptic plasticity, longterm facilitation produced by serotonin (5HT) in Aplysia.…”
mentioning
confidence: 99%
“…The preparation of visual cortical slices from young (P28 À P30) and adult (P50) male WT, floxMecp2, PV-Cre;Ai9 (control) or PV-Mecp2 À /y ;Ai9 mice and whole-cell recording from V1 layer 4 neurons followed a method described in our previous studies 34,35 . The different genotype mice at designed postnatal ages were anaesthetized with sodium pentobarbital (50 mg g À 1 ) and decapitated.…”
Section: Methodsmentioning
confidence: 99%
“…The V1 layer 4 is the main thalamorecipient lamina that transfers visual information into the cortex. In this sets of experiments, we specifically targeted PV cells in cortical slices by the expression of tdTomato in PV-Cre;Ai9 and PV-Mecp2 À /y ;Ai9 mice, while in the brain slices from WT or flox-Mecp2 mice, the cortical fast-spiking PV cells were initially identified by their rough morphology under the infrared camera and further confirmed by their intrinsic non-accommodating ARTICLE high-rate firing pattern and reconstructed morphology after the recording [33][34][35] . Excitatory PCs in the same layer were easily identified by their clear apical dendrites and low firing rates with adaptation.…”
Section: Pv-mecp2mentioning
confidence: 99%
“…Recent studies in several species have shown that spontaneous release also contributes to other synaptic effects, including some cases of homeostatic scaling (Sutton et al 2004(Sutton et al , 2006(Sutton et al , 2007Frank et al 2006Frank et al , 2009Dickman and Davis 2009;Zhang et al 2009;Lee et al 2010;Nosyreva et al 2013). Scaling in those cases has additional similarities to intermediate-and long-term facilitation in Aplysia: Both types of plasticity can involve postsynaptic Ca 2+ , protein synthesis, AMPA receptor insertion, and modulation of the presynaptic probability of release.…”
mentioning
confidence: 99%